Invited review: Interplay of rumen microbiome and the cattle host in modulating feed efficiency and methane emissions - Ajay Badhan; Yue Wang; Stephanie Terry; Robert Gruninger; Le Luo Guan; Tim A. McAllister (Journal of Dairy Science)
ABSTRACT: Given that the majority of energy and protein supplied to cattle arises as a result of ruminal fermentation, the rumen microbiome plays a key role in determining host feed efficiency and methane (CH4) emissions. Some reports suggest that a less diverse rumen microbiome is associated with improved feed efficiency, whereas other studies suggest that microbial diversity does not differ between low- and high-efficiency cattle of the same breed, fed identical diets. Although reducing enteric CH4 emissions offers a dual benefit in terms of improved feed efficiency and a reduced environmental footprint, recent findings indicate that these outcomes are not always consistent in ruminants. The composition of the rumen microbiome is mainly determined by diet but is also influenced by host genetics and physiological parameters such as rumen volume, rate of passage, and rumination. Reduced microbial diversity may impair the ability of cattle to adapt to frequent changes in diet and the environment. Hydrogen exchange and capture are the energetic foundation of the rumen microbiome, and considerable resources have been invested in developing additives that redirect hydrogen flow toward alternative sinks and away from the reduction of CO2 to CH4. These additives reduce enteric CH4 emissions by 30% to 80%, yet the anticipated gains in feed efficiency remain inconsistent. Strategies to improve the feed efficiency of cattle production must consider the multifaceted interactions among the host, rumen microbiome, and diet to ensure the sustainable intensification of cattle production while maintaining the social license for milk and meat production.